O papel dos padrões entoacionais na construção de sentido na leitura oral do professor em sala de aula - Santos, Luciana Virgínia Prazeres Teixeira (2010)
For some peoples, the act of reading is seem easy and pleasant for others is a sacrifice without favorable prospects. School practices often do not prepare the student to be a proficient reader, but to perform a ritual of the curriculum of Portuguese Language. The read result of organized thought, prior knowledge and shared in the interactive action to which they add the linguistic-prosodic features (stretches, tones, change the pace and the time of the voice) and (repetition, pausing, hesitation and interruption). This research is a qualitative analysis of reading shared between teacher and student. It is based on discourse analysis, taking as its starting point the Interactional Theory of Intonation (TIE) of Brazil (1985), who realizes that the clues provided by the reader / listener / author / text are constitutive of meaning and tone choices made by persons, aid in the construction of meaning in spoken language and this sense is directly linked to the understanding of written text. When there is constructionof meaning in oral language, has been a reflection of deconstruction in the writing process. The corpus for this research consists of reading from two different text types: a chronic Discovery (1991), written by Luis Fernando Verissimo, and the poem Sobradinho, of the authors Sa e Guarabira (1973). Two criteria were established for the choice of texts. First, because the chronic and the poem are the object of study covered in the syllabus of classes of the 7th year of fundamental education. Second, because the chronic kind, has a captivating episode, the plot involves a series of actions, with brief and reflective approach, with digressions, comments or notes essay. And the poem, because it has characteristics like melody, rhythm and rhyme, producing harmony, moving between the syllables and unstressed syllables. It was also evidenced the distinct choices of standard intonation, as well as words prominence and impact of those choices in the comprehensive analysis of text. It was noticed that the pause, repetition, hesitation, stretching, exchanges and deletions of words change the meaning of understanding, and concluded that the language resources and para play an essential role in the construction of meaning of text. And when the teacher does not make use of these prosodic strategies as tools in the interactive process, makes the construction of meaning of text.